Association of Shock Index and Modified Shock Index with Mortality Rate in Emergency Department Trauma Patient: Shock Index and Mortality - Zehra, Areej; Ahmed, Farah; Zaidi, Yasmeen Fatima; Khan, Umaima; Rauf, Rabia; Mohyuddin, Samina (Pakistan Journal of Health Sciences, 2024)
At the emergency room, triage was used to determine which patients were more seriously injured and in need of urgent care. Trauma remains one of the primary causes of morbidity and death even with the use of modern triage techniques. Objective: To find out the relationship between trauma patients' 48-hour mortality and the shock index and modified shock index at Emergency Departments (EDs). Methods: A study was conducted in the Emergency Ward of Ziauddin University Hospital, focusing on patients aged 18-65 who sustained trauma. The study involved 50 trauma patients admitted to a Level I trauma center. Data were collected on heart rate, blood pressure, and shock indices at the time of admission. A shock index cut-off value of 0.9 was used to determine its association with patient outcomes. Data collection involved patients visiting the emergency department, with informed consent obtained. SPSS version 21.0 was used for analysis. Results: The study involved 50 patients, with 25 in each exposed and unexposed group. Exposed patients had a higher average age, higher heart rates, and lower blood pressure. Road traffic accidents were the leading trauma mechanism in both groups. Open wounds were more common in exposed patients. Most exposed patients received intravenous fluids and inotropic support. Patients with a Shock Index ≥ 1 and a Modified Shock Index ≥ 1.3 had higher mortality rates. Conclusion: The study revealed a significant link between medical mortality in older adults and bruises in emergency departments, indicating that SI and Modified SI were effective markers for severity assessment.